Геометричні та графічні комп’ютерні моделі у навчальному процесі - Хоменко, Інна Володимирівна (НТУ "ХПІ", 2015)
Проаналізовано сучасні проблеми графічної підготовки, зокрема виділено характерні риси сучасної графічної підготовки. Розглянуто геометричні та графічні комп’ютерні моделі, які використовуються у комп’ютерно-інтегрованому проектуванні та дизайні. Оцінені можливості автоматизації побудов тривимірних моделей та геометричних операцій, методи та засоби геометричних побудов. Визначено важливість параметризації геометричних моделей, як такої, що забезпечує варіантність моделей. Результати досліджень можуть бути використані при створенні систем автоматизованого навчання проектуванню та дизайну, зокрема створенню баз геометричних моделей для практичних занять.

Analyzed the current problems of graphic preparation, particularly highlighted features of modern graphics training. We consider the geometric and graphic computer models used to design and design. The methods and means of geometric modeling of bulk solids, including methods for con-structing three-dimensional models and geometric operations. Determined importance parameterization geometric patterns, as such, providing vari-ance models. The basic task of the work–design and implementation of information technology for the synthesis of structural geometric models to automate training engineering students, including the creation of geometric accuracy and control playback of image models. Developing and improving the efficiency of industrial production directly related to the introduction of new information technology (IT), which is constrained from want of qualified specialists. Young professionals, in addition to knowledge, must have practical skills of computer technology in engineering activities. For efficient organization of educational process in schools should ensure the availability of modern software and hardware for industrial use, and appropriate to their level methodologies.
Geometric and graphic computer models in the educational process
Keywords: автоматизоване навчання проектуванню; інженерний дизайн; графічна підготовка; бази геометричних моделей; automated learning design; learning process; engineering design; geometric patterns and graphic